Dbx1 is a dorsal midbrain-specific determinant of GABAergic neuron fate and regulates differentiation of the dorsal midbrain into the inferior and superior colliculi - Tran, Hong-Nhung; Nguyen, Quy-Hoai; Jeong, Yongsu (Frontiers in Cell and Developmental Biology, 2024)
The mechanism underlying the differentiation of the dorsal midbrain into two morphologically and functionally distinct compartments, the inferior colliculus (IC) and superior colliculus (SC), which process auditory and visual information, respectively, remains largely unexplored. By using null and conditional alleles, we uncover the roles of a homeodomain transcription factor Dbx1 in the regulation of IC and SC differentiation. We show that Dbx1 regulates GABAergic neuron development in the dorsal midbrain. In the absence of Dbx1 function, the dorsal-most m1-m2 progenitor domains in the midbrain fail to activate GABAergic neuron-specific gene expression and instead switch to a glutamatergic phenotype. These results identify Dbx1 as a dorsal midbrain-specific GABAergic determinant that regulates the selector genes, Helt, Gata2, and Tal2. Furthermore, we demonstrate that maturation of the dorsal midbrain into the IC and SC is dependent on Dbx1. Null mutation of Dbx1 impairs the identity and fate of IC and SC neurons. Surprisingly, Dbx1 is required for preventing IC into SC fate switch and thus Dbx1-deficient IC neurons undergo acquisition of SC identity. Conditional inactivation of Dbx1 at late developmental phase leads to alteration in the identity and fate of the IC, but not the SC.These results suggest that SC differentiation is dependent on the early function of Dbx1, and that the IC requires the prolonged action for its normal formation. Furthermore, we uncover that Tcf7l2 acts downstream of Dbx1 selectively to promote IC differentiation.Altogether, our study identifies a molecular mechanism underlying spatial and temporal control of dorsal midbrain development.